EVALUASI KANDUNGAN ASAM ASKORBAT DAN GULA DALAM SARI BUAH LEMON TAIWAN (Citrus depressa H.) - dinar saputri; Sahri Yanti; Hung-Yu Lins2; Wei-Jyun Chien (Faculty of Agricultural Technology, 2023)
This study aimed to determine the content of vitamin C and sugar composition in Citrus depressa H. (CDH) fruit from Taiwan at different levels of ripeness. Analysis of vitamin C was carried out using UV spectrophotometer method, total soluble solid using a brix refractometer, and sugar composition using an HPLC ELSD. The results showed that CDH possess higher amount of vitamin C and lower sugar than other fruits in previous researches. Ripe CDH contains higher vitamin C than unripe fruit. The concentration of the sugar component in unripe CDH is different than the ripe fruit, where the sucrose content increases as the fruit is more ripe.